Pengaruh Komitmen Organisasi, Lingkungan Kerja, Dan Kompensasi Terhadap Kinerja Karyawan (LPD) Pakraman Pedungan - Utami, Ni Made Satya; Saraswati, Ni Putu Ayu Sintya; Putri, Ni Ketut Devi Antari (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
Good performance is needed by every company to achieve the goals that have been set. The study aims to determine the effect of organizational commitment, work environment, and compensation on employee performance at LPD Pakraman Pedungan. Research population of all employees of LPD Pakraman Pedungan as many as 32 employees. The technique of collecting research samples is saturated sampling. Data were collected through a questionnaire with a Likert scale of 1-5. The data analysis technique used is multiple linear regression analysis. The results of research organizational commitment (X1), work environment (X2), and compensation (X3) have a positive effect on employee performance LPD Pakraman Pedungan. Hypothesis testing results: H1: organizational commitment has a positive and significant effect on employee performance (significance value 0.013 < 0.05). H2: the work environment positively and significantly affects employee performance (significance value 0.008 < 0.05). H3: compensation positively and significantly affects employee performance (significance value 0.032 < 0.05).